Structure-activity relationships of thiadiazole agonists of the human secretin receptor - Robert Ardecky; Daniela G. Dengler; Kaleeckal G. Harikumar; Mathew M. Abelman; Jiwen Zou; Bryan A. Kramer; Santhi Reddy Ganji; Steve Olson; Alina Ly; Nikhil Puvvula; Chen-Ting Ma; Raghuveer Ramachandra; et al. (SLAS Discovery, 2024)
Agonists of the secretin receptor have potential applications for diseases of the cardiovascular, gastrointestinal, and metabolic systems, yet no clinically-active non-peptidyl agonists of this receptor have yet been developed. In the current work, we have identified a new small molecule lead compound with this pharmacological profile. We have prepared and characterized a systematic structure-activity series around this thiadiazole scaffold to better understand the molecular determinants of its activity. We were able to enhance the in vitro activity and to maintain the specificity of the parent compound. We found the most active candidate to be quite stable in plasma, although it was metabolized by hepatic microsomes. This chemical probe should be useful for in vitro studies and needs to be tested for in vivo pharmacological activity. This could be an important lead toward the development of a first-in-class orally active agonist of the secretin receptor, which could be useful for multiple disease states.